On companding techniques for PAPR reduction in DCT SC-FDMA system in the presence of CFOs - Naim Ben Ali; Shri Ramtej Kondamuri; Venkata Sainath Gupta Thadikemalla; Srikar D; Pavel Trojovský; Vijaya Durga Chintala (Alexandria Engineering Journal, 2023)
In the single carrier frequency division multiple access (SC-FDMA) system, the use of discrete cosine transform (DCT) instead of discrete Fourier transform (DFT) has shown improved bit error rate (BER) performance. Nevertheless, peak-to-average power ratio (PAPR) in the DCT-based SC-FDMA system is higher than that in the DFT-based system. This paper investigates the performance of various companding schemes to reduce PAPR in DCT-based SC-FDMA systems by considering carrier frequency offsets (CFOs). Simulation results, considering parameters like BER, PAPR, and power spectral density (PSD), are provided to find the best companding technique. Furthermore, the results have been validated in a real-time indoor channel using a wireless open-access research platform (WARP) hardware.